The pharmacotherapy preferred by doctors in treatment of patients diagnosed with asthma or chronic obstructive pulmonary disease or allergic rhinitis and concomitant diseases: an epidemiological analysis - Nowak, Marcin; Brożek, Grzegorz; Doniec, Zbigniew; Olszanecka-Glinianowicz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: The clinical course of asthma and chronic obstructive pulmonary disease (COPD) is influenced by the co-occurrence of other chronic diseases and their pharmacotherapy. There are no data associated with the doctors’ pharmacotherapy preferences in treatment of patients with asthma, COPD or allergic rhinitis and concomitant diseases. Aim : The assessment of doctors’ preferences in pharmacotherapy of asthma, COPD or allergic rhinitis in relation to concomitant diseases. Material and methods : General practitioners, pulmonologists, allergists, laryngologists and paediatricians (n = 319) participated in a questionnaire survey concerning their preferences in pharmacotherapy of asthma, COPD and allergic rhinitis in relation to concomitant diseases enrolling 11,310 patients with asthma, COPD and allergic rhinitis. Results : The concomitant diseases were reported in 58.5% of patients with asthma, 80.8% of patients with COPD and 46.4% of patients with allergic rhinitis. Patients with asthma were most frequently treated with inhaled glucocorticosteroids. However, in the subgroups with concomitant diseases, an increased usage of inhaled long-acting β 2 -mimetics was noted. Regardless of comorbidities, patients with COPD were most frequently treated with inhaled long-acting β 2 -mimetics whereas patients with allergic rhinitis – with nasal glucocorticosteroids and third-generation antihistamines. Conclusions : The co-occurrence of chronic diseases was most frequent among patients diagnosed with COPD. The treatment of asthma, COPD and allergic rhinitis is consistent with international recommendations and the occurrence of concomitant diseases did not significantly influence therapeutic preferences and decisions.